Digital Mind Mapping as a Technique in Teaching Writing: The Use and Response - Elhawwa, Tazkiyatunnafs (SALEE: Study of Applied Linguistics and English Education, 2022)
Writing is the study of how a sentence is arranged or the connection between two parts of a piece of writing. In my previous study, students who got difficulty in writing because they cannot write their idea on paper, they stuck in organizing thoughts, using sequence and logic, and expressing their ideas. This research belonged to descriptive research. The instruments used in the study were closed and open-ended questionnaires, analysis of learners' papers, and observations. Based on the result of the use of digital mind mapping, it showed that students who applied digital mind mapping got more creative, and find a simplify difficult concept in using their mind to think about what the important information should be in the writing a technique used in starting the writing and planning of writing. Based on the students’ responses, almost all participants agree that digital mind mapping was appropriate as one of the techniques in writing class, especially for computer science majors. Lastly, the proper way conducted in writing can help learners easier understand additional data for a particular reason, for example, graphs and pictures.